Pancreatic surgery in elderly patients: results of 329 consecutive patients during 10 years - Bozkurt, Emre; Özoran, Emre; Özata, İbrahim Halil; Bilgiç, Çağrı; Kaya, Mesut; Tüfekçi, Tutku; Tellioğlu, Gürkan; Bilge, Orhan (Frontiers in Medicine, 2023)
Introduction: There is a progressive shift from a younger population to an older population throughout the world. With the population age shift surgeons will be more encounter with an older patient profile. We aim to determine age-related risk factors of pancreatic cancer surgery and the effect of patient age on outcomes after pancreatic surgery. Material and Methods: A retrospective review was conducted with data from a consecutive 329 patients whose pancreatic surgery was performed by a single senior surgeon between the dates of January 2011 and December 2020. Patients were divided into three groups based on age; patients younger than 65 years old, between 65 and 74 years old and older than 74 years old. Demographics and postoperative outcomes of the patients were evaluated and compared between these age groups. Results: The distribution of a total of 329 patients into the groups was 168 patients (51.06%) in Group 1 (age <65 years old), 93 patients (28.26%) in Group 2 (age 65 and <75 years old), and 68 patients (20.66%) in Group 3 (age  75 years old). The overall postoperative complications statistically significantly higher in group 3 than group 1 and 2 (p=.013). The comprehensive complication index of the patients in each group was 23.16.8, 20.48.1 and 20.5+6.9, respectively (p=0.33). Fisher’s exact test indicated a significant difference in morbidity in patients with ASA 3–4 (p=.023). In hospital or 90-day mortality was observed in 2 patients (0.62%), one from group 2 and one from group 3. 3-year survival rates were 65.4%; 58.8%; and 56.8%, respectively, for each group (p=.038). Conclusion: Our data demonstrate that comorbidity, ASA score and the possibility of achieving a curative resection do have significantly more impact than age alone.